Analisis Yuridis Prinsip Tanggung Jawab Komando dalam Konflik Bosnia Berdasarkan Hukum Pidana Internasional: Studi Yurisprudensi ICTY (International Criminal Tribunal for the Former Yugoslavia) - Tenti Ayu; Dwi Putri Lestarika (Lembaga Yasin AlSys, 2026)
The principle of command responsibility is an important doctrine in international criminal law that allows military commanders to be held accountable for crimes committed by subordinates under their control. This doctrine is grounded in the concept of hierarchical accountability, namely the obligation of superiors to prevent, supervise, and take action against violations of international humanitarian law. This study aims to analyze the normative construction and application of the principle of command responsibility in the Bosnia conflict of 1992–1995 based on the jurisprudence of the International Criminal Tribunal for the former Yugoslavia (ICTY), as well as to assess its conformity with the principle of legality and the principle of culpability in international criminal law. This study employed a normative juridical method with statutory, case, and conceptual approaches. The results show that the main elements of command responsibility include the superior-subordinate relationship, effective control, and the knowledge element (knew or should have known), all of which must be proven factually. The ICTY affirmed that responsibility does not arise automatically from formal position, but rather from the actual ability to control and prevent crimes. Although there is debate regarding the limits of the interpretation of effective control and the should have known standard, the application of this doctrine in the Bosnia cases generally remained within the framework of the principles of nullum crimen sine lege and nulla poena sine culpa. These findings indicate that the principle of command responsibility in ICTY jurisprudence is consistent with the fundamental principles of international criminal law and strengthens the legitimacy of this doctrine in enforcing command criminal accountability.